Learning from virtuality in the inverted classroom model: an experience in university education (Technological Innovations Journal, 2022)
The objective was to analyze learning from virtuality in the inverted classroom model that was used in the Master of Administration of Micro, Small and Medium Enterprises of the Autonomous University of Sinaloa to identify the most suitable virtual learning environments. With a qualitative, exploratory and descriptive approach, documentary analysis was developed, under the ethnographic and action-research method, participant observation, a convenience survey with a Cronbach's Alpha test questionnaire and interviews with a sample of 18 students were applied. graduate with a confidence level of 95%. The results show that in Sinaloa there is no digital capillarity and not all Master's students have connectivity to develop the flipped classroom model. After the pandemic, students consider that it is a model that enhances the development of their learning and strengthens self-management, self-regulation and self-efficacy skills in the different virtual learning environments. The digital maturity of the students offers arguments to define the virtual transformation in the postgraduate programs of the University. The hypothesis that graduates students reject the model as a product of skepticism and intolerance is discarded; but rather, due to the lack of specialized technological equipment and the lack of connectivity.
Keywords: virtual learning environments; inverted classroom; ICT; virtuality